Dietary intake and blood lipid profile in overweight and obese schoolchildren - Rinaldi, Ana Elisa Madalena [UNESP]; De Oliveira, Erick Prado [UNESP]; Moreto, Fernando [UNESP]; Gabriel, Gleice Fernanda Costa Pinto [UNESP]; Corrente, José Eduardo [UNESP]; Burini, Roberto Carlos [UNESP] (Springer Nature, 2012)
Abstract. Background: The high blood lipid levels and obesity are one of the main risk factors for cardiovascular diseases, and the atherosclerotic process begins in childhood. Some environmental factors are supposed to be involved in this relationship, such as dietary factors. This study aimed to investigate the relationship between dietary intake and blood lipids levels in overweight and obese schoolchildren. Methods. This is a cross-sectional study with 147 overweight and obese schoolchildren in Botucatu city, Brazil. The anthropometric measurements (body weight, height, body mass index, waist circumference and skinfolds), pubertal staging evaluation and biochemical tests were taken in all children. Three 24h-recall were applied in order to estimate the dietary intake and its relationship with blood lipid levels. The Student t test and multiple linear regression analysis were used for statistical analysis. Statistical significance was assessed at the level of 0.05. The data were processed in SAS software (version 9.1.3; SAS Institute). Results: At this study, 63% of children were obese (body mass index higher than 95§ssup§th§esup§ percentile) and 80% showed high body fat percentage. The percentage of children with abnormal total cholesterol and triglycerides was 12% and 10%, respectively, and 28% presented at least one abnormal lipid levels. The average values of anthropometric measurements were higher in children with elevated lipid levels. Total cholesterol levels were positively related to full-fat dairy products and triglycerides levels to saturated fat percentage. Conclusions: Saturated fat was positively associated with elevated lipid levels in overweight and obese schoolchildren. These results reinforce the importance of healthy dietary habits since childhood in order to reduce the risks of cardiovascular diseases in adulthood. © 2012 Rinaldi et al.; licensee BioMed Central Ltd.
Keywords: Blood lipid; Body mass index; Food consumption; Schoolchildren; lipid; anthropometry; blood; Brazil; child; cross-sectional study; diet; female; human; male; obesity; pathophysiology; Anthropometry; Child; Cross-Sectional Studies; Diet; Female; Humans; Lipids; Male; Obesity; Overweight